Investigation Of the Anti-Inflammatory and Immunomodulatory Effects of Garlic, Onion, And Lemon Extracts in Pulmonary Disorders - Dhumal, Jeevan Suresh; Hema Sri, Manepalli; Dhakad, Krati; Singh, Ankita; Rajora, Priyanka Singh; Narapusetty, Naidu; Kumari, Kamini; Shaik, Mobeen; Deshpande, Mangirish (Journal of Neonatal Surgery, 2025)
Pulmonary disorders, characterized by inflammation and immune dysregulation, represent a significant global health burden with limited effective therapeutic options. This investigation explores the anti-inflammatory and immunomodulatory effects of natural extracts from garlic (Allium sativum), onion (Allium cepa), and lemon (Citrus limon) in pulmonary diseases. Garlic extract, rich in organosulfur compounds such as diallyl trisulfide, exhibits potent suppression of inflammatory pathways including NF-κB and the NLRP3 inflammasome, reducing cytokine production and inflammatory cell infiltration in lung tissues. Similarly, onion extract demonstrates bronchodilatory, antiallergic, and anti-inflammatory properties mediated through cytokine modulation, reduction of Th2 responses, and inhibition of oxidative stress. Lemon extract contributes antioxidative and immune-regulating effects primarily via bioactive flavonoids like hesperidin and eriocitrin, enhancing antioxidant defenses and mitigating inflammatory cytokines in the pulmonary environment. Collectively, these extracts modulate key inflammatory and immunological pathways, including cytokine secretion, inflammasome activation, and oxidative stress, thereby alleviating pulmonary inflammation and enhancing immune homeostasis. This integrative study underscores the therapeutic potential of garlic, onion, and lemon extracts as complementary interventions for pulmonary disorders, warranting further clinical evaluation for safe and effective application in respiratory disease management..